Harmonisasi Kebijakan Pajak dan Prinsip Keadilan Sosial dalam Meningkatkan Kesejahteraan Nasional - Rifa Tafa’ul Ula; Farid Rizqi Ananda (Journal of Legal, Political, and Humanistic Inquiry, 2025)
This study examines the harmonization of tax policy with the principle of social justice as a foundation for achieving national welfare in Indonesia. Using a normative juridical approach, the analysis focuses on legal norms contained in tax legislation, the implementation of redistributive mechanisms, and their alignment with the constitutional mandate of social justice. The study also incorporates empirical indicators such as the Gini Ratio and expenditure distribution of the bottom 40 percent to evaluate the real impact of taxation on economic equality. Findings show that although Indonesia’s tax framework embodies progressive principles, the outcomes remain limited due to weak institutional capacity, low tax literacy, and unequal enforcement. The national Gini Ratio only decreased slightly from 0.379 in 2024 to 0.375 in 2025, indicating a modest redistribution effect. These results highlight the need for comprehensive reform through simplification of tax regulations, strengthening of fiscal transparency, and increased public participation. A harmonized, equitable, and accountable tax system is essential to sustain inclusive and just economic growth